2017
DOI: 10.1371/journal.pone.0184068
|View full text |Cite
|
Sign up to set email alerts
|

Tankyrase inhibitors suppress hepatocellular carcinoma cell growth via modulating the Hippo cascade

Abstract: Previous data indicate that Tankyrase inhibitors exert anti-growth functions in many cancer cell lines due to their ability to inactivate the YAP protooncogene. In the present manuscript, we investigated the effect of Tankyrase inhibitors on the growth of hepatocellular carcinoma (HCC) cell lines and the molecular mechanisms involved. For this purpose, we performed cell proliferation assay by colony-forming ability in seven human HCC cells subjected to XAV-939 and G007-LK Tankyrase inhibitors. Noticeably, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 49 publications
3
40
0
Order By: Relevance
“…At days 4–5, cell proliferation was reduced, while apoptosis significantly elevated along with a drastically decrease of ISCs in Tnks DKO mice, even at day 2 and day 3 after the first tamoxifen administration. This is consistent with a plethora of studies showing that TNKS inhibitors suppress cell proliferation in several cancer cell lines [ 48 52 ]. Although inhibition of TNKS activity has been shown to block Apc mutant colorectal cancer development [ 53 , 54 ], we found that the organoids derived from the polys of Villin-Cre ; Apc +/fl mice showed normal cell proliferation and activation of Wnt/β-catenin signaling in the presence of XAV939.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…At days 4–5, cell proliferation was reduced, while apoptosis significantly elevated along with a drastically decrease of ISCs in Tnks DKO mice, even at day 2 and day 3 after the first tamoxifen administration. This is consistent with a plethora of studies showing that TNKS inhibitors suppress cell proliferation in several cancer cell lines [ 48 52 ]. Although inhibition of TNKS activity has been shown to block Apc mutant colorectal cancer development [ 53 , 54 ], we found that the organoids derived from the polys of Villin-Cre ; Apc +/fl mice showed normal cell proliferation and activation of Wnt/β-catenin signaling in the presence of XAV939.…”
Section: Discussionsupporting
confidence: 91%
“…The essential role of TNKSs in the maintenance of intestinal epithelium homeostasis is in agreement of the function of Wnt signaling in promoting cell proliferation and inhibiting apoptosis [ 17 ]. The results from previous studies showed the high effectiveness of TNKS inhibitors in inhibiting various cancer cell proliferation including CRC [ 48 , 51 53 ]. However, based on our genetic results and previous pharmacologic results [ 58 ], caution should be taken to the possible toxicity of TNKS inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…ARCs and the SAM domain direct tankyrase to regulators of a wide range of biological processes, among which Wnt/β-catenin signaling (Huang et al 2009 ; Mariotti et al 2016 , 2017 ; Yang et al 2016 ), the maintenance and mitotic resolution of telomeres (Smith et al 1998 ; Smith and de Lange 2000 ; Dynek and Smith 2004 ) and glucose metabolism (Chi and Lodish 2000 ; Yeh et al 2007 ; Zhong et al 2016 ) are some of the best-studied. Additional roles of tankyrase include the regulation of mitotic spindle formation (Chang et al 2005 , 2009 ), Hippo signaling (Wang et al 2015 ; Troilo et al 2016 ; Jia et al 2017 ) and emerging functions in the DNA damage response (Nagy et al 2016 ), cell migration (Lupo et al 2016 ), and Notch signaling (Bhardwaj et al 2017 ), to name a few. Proteomics studies and in-silico predictions of tankyrase binders illustrate the diverse cellular functions of tankyrase (Guettler et al 2011 ; Li et al 2017 ; Bhardwaj et al 2017 ).…”
Section: Biological Contextmentioning
confidence: 99%
“…In breast cancer, AMOTL2 increased LATS kinase activity leading to the suppression of metastasis of tumor cells [23]. Besides, when downregulated, AMOTL2 enhanced tumor cells growth [24], migration and angiogenesis [25] via Hippo pathway in hepatocellular carcinoma. MESRB3 regulates proliferation of MEF cells via enhancing the protein level of p27 [26].…”
Section: Discussionmentioning
confidence: 99%